Description of three new species of Tardigrada from the Seychelles - Pilato, Giovanni; Lisi, Oscar (Zootaxa, 2009)
In the context of the project “The Nature Protection Trust of Seychelles”, three species new to science are described: Calcarobiotus (Calcarobiotus) parvicalcar sp. n., Macrobiotus modestus sp. n., and Itaquascon pisoniae sp. n. Calcarobiotus (Calcarobiotus) parvicalcar sp. n. differs from the other species of the genus in having very small basal spurs of the claws; from some of them also in lacking eyes or in metric characters of placoids or claws. Macrobiotus modestus sp. n. has a very simple buccal armature (only three thin transverse ventral ridges are present and the three dorsal ridges are joined together forming a single transverse dorsal arc), and a long and narrow buccal tube with stylet supports inserted at 67–70 % of its length. It differs from the most similar species, Macrobiotus humilis and Macrobiotus madegassus, in some characteristics of bucco-pharyngeal apparatus and eggs. Itaquascon pisoniae sp. n. has the buccal tube slightly longer than the pharyngeal tube (pbf index = 54–55), pharyngeal apophyses and placoids are absent, a very faint cuticular bar near the internal claws of the first three pairs of claws, and no cuticular thickenings on the hind legs. It differs from the most similar species of the genus, Itaquascon placophorum, in having a smooth cuticle, shorter claws, in lacking placoid and the cuticular bar between the claws of the hind legs. Including this study, 30 species are recorded in the Seychelles, 15 of which are currently considered endemic for that archipelago.